Leading K-12 Community Responsiveness to Cyber Threats via Education of School Community - Michele Kielty; A. Renee Staton (Journal of Cybersecurity Education, Research & Practice)
Cyber threats have escalated in recent years. Many of these threats have been direct and vicious attacks on K-12 systems. Educators are rarely trained on how to address cyber threats from a systemic and educational perspective when such challenges arise in their school buildings. This article explains the cyber threats that are looming large for K-12 systems and provides concrete tools for school leaders to employ in order to provide preventive education to their school communities.